Existence of Solutions of Boundary Value Problems for Fractional Differential Equations with p-Laplacian Operator in Banach Spaces. (3rd June 2017) - Tan, Jing-jing; Cheng, Cao-zong
ABSTRACT: In this paper, we consider the existence of solutions for systems of nonlinear p-Laplacian fractional differential equations whose nonlinearity contains the first-order derivative explicity in Banach space E, where 𝜃 is the zero element of E, φ p is the p-Laplacian operator, i.e., with p >1, its inverse function is denoted by φ q with, and p, q satisfy, is standard Caputo derivative and f : I × E × E → E is continuous. Our main tool is the Sadovskii fixed point theorem.